ANALYSIS OF THE PRODUCTION COST OF A UNIT OF BIODIESEL PRODUCTION IN THE BIODIESEL PLANT - Batić, Iva; Babić, Miroljub (Economics of Agriculture, 2025)
Biodiesel is defined as mono-alkyl ester of fatty acids obtained from vegetable oils or animal fats. In this paper, an analysis of the cost of the production of a unit of biodiesel is given. It is shown which parameters affect the cost price of the unit of this product produced in the biodiesel plant. Analyzed biodiesel plant is in Skopje in North Macedonia with a projected capacity of 20,000 tons of biodiesel per year. Also, a comparative analysis of different cases was done: the case where during the design and implementation of the production plant the capacity of the production plant would be increased to the level of 25,000 tons, as well as to the level of 30,000 tons of produced biodiesel. It was also shown how the use of a sufficient level of soybean oil would affect the cost of the unit of the biodiesel product.